please see this question and explain with example

Hi,

The steps are clearly explained as

Taking simple examplea+b2= a2+2ab+b2Last term =3rd term =   total number of terms -0 = 3-1-1as 0 can be written as 1-1 and we are doing this to get a seneral formula. So second term from the last =2nd term= total number of terms -1= 3- 2-1Similarly for , a+b3= a3+3a2b+3ab2b2+b3Last term =4th term =   total number of terms -0 = 4-1-1as 0 can be written as 1-1 and we are doing this to get a seneral formula. So second term from the last =3rdterm= total number of terms -1= 4- 2-1and so on So here you must proceed the same and remeber that Formula is impotent so remeber the result. Regards

  • -2
rth term from the end is n-r+2 
  • 0
What are you looking for?